Immunological Responses to Helminths and HIV-1 Co-Infections - Chavura, Elton; Singini, Wales; Chidya, Russel; Mbakaya, Balwani Chingatichifwe (European Scientific Journal, ESJ, 2023)
Helminth infections result from either ingestion or contact with contaminated fecal matter. To date, there is insufficient evidence as to whether helminths have influence on HIV-1 specific immune responses as literature results are indeterminate. We evaluated the effect of helminth infections on HIV disease progression through the monitoring of 2 outcomes: (1) plasma HIV-1 RNA Viral load (V/L) and (2) Cluster of Differentiation (CD4+) T-lymphocyte count amongst helminth-HIV-1 co-infected persons. We hypothesized that (1) concurrent helminth infections may damage immune control, resulting in escalating VL and reduced CD4+ T-lymphocyte count (2) and that, subject to successful treatment, a decrease in plasma VL could slow down disease progression. We reviewed 2032 citations, evaluated 432 abstracts, and read 10 articles (See PRISMA diagram). The methodologies were appraised using a Mixed Method Appraisal Tool (MMAT). At enrolment, plasma VL were significantly higher in individuals with helminths (5.01 log10 vs. 3.41 log10, p < 0.001). The magnitude of effect ranged from 5.28 log10 copies/mL at baseline and 4.67 log10 copies/mL, (p < 0.05) after treatment and a trend for 0.61 log10 lower VL. All but one RCT reported decline in plasma VL and significant interactions were seen in the successfully treated groups (p < 0.001). CD4+ T-lymphocyte count values were not significantly different in the co-infection groups relative to those with HIV-infection alone. This evidence supports that WaSH and HIV/AIDS co-programming could promote health of PLWHA. We suggest large scale trials for future studies. This systematic review registration number is CRD42022364296.